Hybrid Contract Implementation in Multi Payment Product Services: Implementasi Kontrak Hibrida dalam Layanan Produk Multi Pembayaran - Ananda Putri Savana; Tuti Anggraini; Rahmi Syahriza (Academia Open, 2025)
General Background: The increasing complexity of financial needs has driven the demand for Sharia-compliant services that balance efficiency with ethical principles. Specific Background: Pegadaian Syariah has adopted hybrid contracts in its Multi Payment Online (MPO) product to meet these demands. Knowledge Gap: While hybrid contracts are increasingly used, limited research explores their local implementation in non-bank Islamic financial institutions, particularly Pegadaian Syariah. Aims: This study aims to evaluate the effectiveness of hybrid contract implementation in the MPO product at Pegadaian Syariah A.R. Hakim Medan, identify operational challenges, and assess the influence of public understanding, outreach, and technology. Results: The findings confirm that the contracts adhere to MUI fatwas and Sharia principles under DPS supervision, but challenges include network issues and fluctuating provider margins. Novelty: This research offers an applied perspective on hybrid contract structuring in a localized context, combining multiple contract types (wakalah, ijarah, qardh) for service integration. Implications: The study suggests that enhanced digital infrastructure, public education, and proactive contract renegotiation are crucial for optimizing service delivery, offering valuable insights for scaling hybrid-based financial products in other Islamic finance settings.Highlight : The main focus of the research is the application of hybrid contracts in MPO products at Pegadaian Syariah Branch A.R. Hakim Medan. The main challenges include network disruptions and changes in service margins that require renegotiation of the contract. The role of technology and digital socialization proved important in service effectiveness and public understanding. Keywords : Hybrid Contract, Multi Payment, Analysis, Pegadaian Syariah, Digital Transaction